British-Muslim identity : self-questioning hybridity in Hanif Kureishi’s The Black Album and Monica Ali’s Brick Lane. - Koh, Rachel Hui Ling. (2009)
This paper investigates the British-Muslim identity in Hanif Kureishi's The Black ALbum and Monica Ali's Brick Lane. I will also discussion the need for self-exile in order to discover a multiplicity of the British-Asian identity with respect to both their natal and foster cultures.